Marilyn Wood's Wonderful weekends - Wood, Marilyn (New York : Simon & Schuster, Inc., 1984)
Each chapter below contains descriptions of the following: getting there, special events & festivals, attractions, inns, hotels, bed & breakfast /brunch places, saturday luncheon choices, romantic dining, evening entertainment, and activities.
Connecticut -- Massachusetts -- New jersey -- New York -- Pennsylvania & delaware -- Rhode island -- Vermont.
Keywords: MIDDLE ATLANTIC STATES -- DESCRIPTION AND TRAVEL -- GUIDE BOOKS